The Role of Stakeholders in Sustainability Reporting Assurance - Manetti, Giacomo; Toccafondi, Simone (2012)
The main purpose of this exploratory analysis is to understand whether, based on evidence gathered from international best practices selected among corporations which adopt the Global Reporting Initiative guidelines in sustainability reporting (SR), stakeholders are significantly consulted and involved—as international literature would indicate—by assurance providers, during assurance processes of SR. We aim at verifying if this practice—known as stakeholder assurance—is in fact widespread in SR assurance by carrying out empirical research, through content analysis, into a sample of 161 assurance statements of international corporations, in order to test characteristics of any stakeholder assurance implemented.
Keywords: Sustainability reporting; Stakeholder engagement; Global Reporting Initiative; Content Analysis; Assurance